(3GdJMOjGJ GdJj JhGLg efXeGJ GdCYeGd GdeYGUQI (B:s (3GdCReI GdeGdjI hGdYGdejI hGdCaGb GdeSJbHdjI (B/s - (3GdRjGOGJ, eMeOs; (3GdYHGOj, SejQs ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj(B, s, 2011)
(3GdSjGSI GdeGdjI aj GdGQOf h GdGReI GdeGdjI GdGbJUGOjI GdYGdejI , GdGSJKeGQ aj GdeTGQjY GdUZjQI h OhQg aj GdMO ef JCKjQ GdGReI GdeGdjI aj GdGQOf , GKQ GdeNGWQI GdfXGejI aj GdYGFO GdRGFO ddGSge GdYGOjI , BKGQ GdGReI GdeGdjI GdYGdejI Ydi UfGOjb GdKhQI GdSjGOjI , fMh JaYjd COhGJ GdSjGSI GdVQjHjI dehGLgI GdGReI GdeGdjI GdYGdejI (B: (3MGdI GdLRGFQ , GdGReI GdeGdjI GdYGdejI , GdeDSSGJ GdeGdjI GdShQjI aj Xd GdGReI GdeGdjI GdYGdejI , OQGSI abgjI dMce GdQgf GdYbGdGj , JOGYjGJ GdGReI GdYGdejI Ydi GdLgGR GdeUQaj GdGQOfj ,eY hLhO CHMGK HGddZI GdGfLdjRjI (B: the implication of unemploment in the united arab emirates and the global economiccrisi:the problem and solution , the impact of the world recent financial crisis on developing countries , the kconcept of business ethics as viewed , islamic financfacing risks of the international financil crisis , managemenet in the light of globalizathon and economic.s
Keywords: (3GdCReGJ GdGbJUGOjIs; (3GdeGdjIs; (3efXeGJ CUMGH GdYeds